2014
DOI: 10.1159/000360071
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Neuroligin-3 and Tyrosine Hydroxylase across the Brain in Mate Choice Contexts in Female Swordtails

Abstract: Choosing mates is a commonly shared behavior across many organisms, with important fitness consequences. Variations in female preferences can be due in part to differences in neural and cellular activity during mate selection. Initial studies have begun to identify putative brain regions involved in mate preference, yet the understanding of the neural processes regulating these behaviors is still nascent. In this study, we characterized the expression of a gene involved in synaptogenesis and plasticity (neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…After all behavioral trials, we returned females to their respective treatment for an additional 2 months prior to tissue collection. We chose this time frame to minimize shortterm effects from mating preference trials, which have previously been studied in other systems and contexts (Bloch et al, 2018;Wong et al, 2012;Wong and Cummings, 2014), and focus our analysis instead on the effects of social exposure on baseline gene expression profiles.…”
Section: Materials and Methods Study System And Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation
“…After all behavioral trials, we returned females to their respective treatment for an additional 2 months prior to tissue collection. We chose this time frame to minimize shortterm effects from mating preference trials, which have previously been studied in other systems and contexts (Bloch et al, 2018;Wong et al, 2012;Wong and Cummings, 2014), and focus our analysis instead on the effects of social exposure on baseline gene expression profiles.…”
Section: Materials and Methods Study System And Experiments Designmentioning
confidence: 99%
“…In addition to examining transcriptome-wide data, we assessed differential expression between B-EXP and M-EXP females in key gene families previously shown to be implicated in social decisionmaking (O'Connell and Hofmann, 2012), mate choice (Cummings, 2015;Wong and Cummings, 2014;Wong et al, 2012;Bloch et al, 2018) and stress-related personality traits (Backstr枚m and Winberg, 2017;Th枚rnqvist et al, 2018). Interestingly, we found that M-EXP females were characterized by greater expression of several genes related to the signaling pathways of dopamine, serotonin, oxytocin and progesterone, as well as neuropeptide receptor-related GPCRs, while B-EXP females mostly showed upregulation of olfactory receptors and MHC-I-like genes (Fig.…”
Section: Exposure Effects On Gene Expressionmentioning
confidence: 99%
“…In recent years, an approach to map a specialized part of the brain by focusing on regions such as the hippocampus, which is involved in learning and memory [78,79], has been developed. A comparison of gene expression profiles among brain regions (e.g., telencephalon, diencephalon, cerebellum) in fish responding to intruders [70] has been attempted, and analyses of changes in the conserved 'social behavior network'-a collection of brain nuclei known to regulate social behaviors across vertebrates-based on detailed micro-dissected brain regions in cichlids [80], zebrafish [81], and swordtail fish [82] have been carried out. The limbic region, midbrain, and the cortical region are involved in a variety of motivations in mice [38,39,83].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…is not due to species differences per se, but that females are responding more to male reproductive tactics than species identity. Finally, in X. nigrensis, females exposed to two courting males show a high correlation in the expression of neuroligin-3 in regions that are associated with social decision making than females exposed to a courting and a coercive male, and little correlation is observed across these regions when females are exposed to two coercive males (Wong and Cummings, 2014), suggesting that interaction with courting phenotypes, more than coercive phenotypes, demand engagement of brain plasticity (Figure 3).…”
Section: Reproductive Status and Plasticitymentioning
confidence: 99%